Mechanisms of RON-mediated epithelial-mesenchymal transition in MDCK cells through the MAPK pathway - Xiangming,Xu (2011)
The epithelial-mesenchymal transition (EMT) is involved in neoplastic metastasis, and the RON protein may be involved. In the present study, we determined the role and the mechanisms of action of RON in EMT in Madin-Darby canine kidney (MDCK) cells by Western blot and cell migration analysis. Activation of RON by macrophage stimulating protein (MSP) results in cell migration and initiates changes in the morphology of RON-cDNA-transfected MDCK cells. The absence of E-cadherin, the presence of vimentin and an increase in Snail were observed in RE7 cells, which were derived from MDCK cells transfected with wt-RON, compared with MDCK cells. Stimulation of RE7 cells with MSP resulted in increased migration (about 69% of the wounded areas were covered) as well as increased activation of extracellular signal-regulated kinase 1/2 (Erk1/2) and glycogen synthase kinase-3β (GSK-3β; the percent of the activation ratio was 143.6/599.8% and 512.4%, respectively), which could be inhibited with an individual chemical inhibitor PD98059 (50 μM) specific to MAPK/ERK kinase (the percent inhibition was 98.9 and 81.2%, respectively). Thus, the results indicated that RON protein could mediate EMT in MDCK cells via the Erk1/2 pathway. Furthermore, GSK-3β regulates the function of Snail in controlling EMT by this pathway.